Cholesterol ester transfer protein inhibition by TA-8995 in patients with mild dyslipidaemia (TULIP): a randomised, double-blind, placebo-controlled phase 2 trial. Issue 9992 (1st August 2015) - Hovingh, G Kees; Kastelein, John J P; van Deventer, Sander J H; Round, Patrick; Ford, John; Saleheen, Danish; Rader, Daniel J; Brewer, H Bryan; Barter, Philip J
Summary: Background: Dyslipidaemia remains a significant risk factor for cardiovascular disease and additional lipid-modifying treatments are warranted to further decrease the cardiovascular disease burden. We assessed the safety, tolerability and efficacy of a novel cholesterol esterase transfer protein (CETP) inhibitor TA-8995 in patients with mild dyslipidaemia. Methods: In this randomised, double-blind, placebo-controlled, parallel-group phase 2 trial, we recruited patients (aged 18–75 years) from 17 sites (hospitals and independent clinical research organisations) in the Netherlands and Denmark with fasting LDL cholesterol levels between 2·5 mmol/L and 4·5 mmol/L, HDL cholesterol levels between 0·8 and 1·8 mmol/L and triglyceride levels below 4·5 mmol/L after washout of lipid-lowering treatments. Patients were randomly allocated (1:1) by a computer-generated randomisation schedule to receive one of the following nine treatments: a once a day dose of 1 mg, 2·5 mg, 5 mg, or 10 mg TA-8995 or matching placebo; 10 mg TA-8995 plus 20 mg atorvastatin; 10 mg TA-8995 plus 10 mg rosuvastatin or 20 mg atorvastatin or 10 mg rosuvastatin alone. We overencapsulated statins to achieve masking. The primary outcome was percentage change in LDL cholesterol and HDL cholesterol from baseline at week 12, analysed by intention to treat. This study is registered with ClinicalTrials.gov, number NCT01970215 . Findings: Between Aug 15, 2013, and Jan 10, 2014, 364 patients were enrolled. At week 12, LDL cholesterol levels were reduced by 27·4% in patients assigned to the 1 mg dose, 32·7% in patients given the 2·5 mg dose, 45·3% in those given the 5 mg dose, and 45·3% in those given the 10 mg dose (p<0·0001). LDL cholesterol levels were reduced by 68·2% in patients given 10 mg TA-8995 plus atorvastatin, and by 63·3% in patients given rosuvastatin plus 10 mg TA-8995 (p<0·0001). A daily dose of 1 mg TA-8995 increased HDL cholesterol levels by 75·8%, 2·5 mg by 124·3%, 5 mg by 157·1%, and 10 mg dose by 179·0% (p<0·0001). In patients receiving 10 mg TA-8995 and 20 mg atorvastatin HDL cholesterol levels increased by 152·1% and in patients receiving 10 mg TA-8995 and 10 mg rosuvastatin by 157·5%. We recorded no serious adverse events or signs of liver or muscle toxic effects. Interpretation: TA-8995, a novel CETP inhibitor, is well tolerated and has beneficial effects on lipids and apolipoproteins in patients with mild dyslipidaemia. A cardiovascular disease outcome trial is needed to translate these effects into a reduction of cardiovascular disease events. Funding: Dezima.